2010
DOI: 10.1055/s-0030-1259090
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Olefins into α-Bromo Ketones Using O-Iodoxybenzoic Acid and Tetraethylammonium Bromide

Abstract: Utilizing full potential of IBX, a mild, selective, and facile method has been developed for the direct conversion of olefins into the corresponding a-bromo ketones by using 1.1 equivalents each of o-iodoxybenzoic acid and tetraethylammonium bromide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…-Bromoketones are important intermediates in the synthesis of various complex molecules. [64][65][66] These 1,2-synthons can be typically accessed from alkenes, 66 alcohols, 67 TMS-enolates, 68 and ketones. 69 We showed that olefins can be converted into -bromoketones by treatment with NBS in the presence of IBX in DMSO.…”
Section: One-pot Transformation Of Olefins Into -Bromo-and -Azidoke...mentioning
confidence: 99%
See 1 more Smart Citation
“…-Bromoketones are important intermediates in the synthesis of various complex molecules. [64][65][66] These 1,2-synthons can be typically accessed from alkenes, 66 alcohols, 67 TMS-enolates, 68 and ketones. 69 We showed that olefins can be converted into -bromoketones by treatment with NBS in the presence of IBX in DMSO.…”
Section: One-pot Transformation Of Olefins Into -Bromo-and -Azidoke...mentioning
confidence: 99%
“…To obviate the use of DMSO, the reaction with IBX (1 equiv) was carried out with tetraethylammonium bromide (TEAB, 1 equiv) as a brominating reagent in anhydrous CH 2 Cl 2 at room temperature. 66 The catalytic protocol avoids stoichiometric usage of IBX and replaces the polar and high-boiling DMSO as the solvent. Accordingly, the cat-…”
Section: One-pot Transformation Of Olefins Into -Bromo-and -Azidoke...mentioning
confidence: 99%